Low Arabian dust extinction-to-backscatter ratio - Mamouri, Rodanthi-Elisavet; Ansmann, Albert; Nisantzi, Argyro; Kokkalis, Panayotis; Schwarz, A.; Hadjimitsis, Diofantos G. (My University, 2013)
[1] Compared to typical values of 50–60 sr of the extinction-to-backscatter ratio (lidar ratio) at 532 nm of western Saharan mineral dust, low dust lidar ratios from 33.7±6.7 to 39.1±5.1 sr were derived from polarization lidar observations at Limassol, Cyprus (34°N, 33°E) during an outbreak of Arabian dust mainly from Syria in September 2011, indicated by particle linear depolarization ratios up to 28%–35%. The applied new polarization-lidar/photometer method for the extraction of the dust-related lidar-ratio information from the lidar data is outlined, and the results of the dust outbreak which lasted over several days are discussed. The results confirm an Aerosol Robotic Network photometer study on Arabian dust lidar ratios.
Keywords: Arabian dust; Lidar ratio